2010
DOI: 10.1089/hum.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Self-Inactivating Lentiviral Vector Integration Sites and Flanking Gene Expression in Human Peripheral Blood Progenitor Cells After Alkylator Chemotherapy

Abstract: Hematotoxicity is a major and frequently dose-limiting side effect of chemotherapy. Retroviral methylguanine-DNA-methyltransferase (MGMT; EC 2.1.1.63) gene transfer to primitive hematopoietic progenitor cells (CD34(+) cells) might allow the application of high-dose alkylator chemotherapy with almost mild to absent myelosuppression. Because gammaretroviral vector integration was found in association with malignant or increased proliferation, novel lentiviral vectors with self-inactivating (SIN) capacity might d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…4). In accordance with previous studies employing lentiviral vectors (Mitchell et al, 2004;Laufs et al, 2006;Grund et al, 2010), in our experiments we found most of the integrations within gene-coding regions; 76.5% in pre-TX samples, 67.4% in treated samples, 60.5% in NT samples, and 74% in control BM samples. Furthermore, among these insertions, 65.4% -4% occurred in introns.…”
Section: Characteristic Lentiviral Integration Profile Observed In Alsupporting
confidence: 93%
See 4 more Smart Citations
“…4). In accordance with previous studies employing lentiviral vectors (Mitchell et al, 2004;Laufs et al, 2006;Grund et al, 2010), in our experiments we found most of the integrations within gene-coding regions; 76.5% in pre-TX samples, 67.4% in treated samples, 60.5% in NT samples, and 74% in control BM samples. Furthermore, among these insertions, 65.4% -4% occurred in introns.…”
Section: Characteristic Lentiviral Integration Profile Observed In Alsupporting
confidence: 93%
“…+ cells transduced with an MGMT lentiviral vector employing the SFFV promoter (Grund et al, 2010). Similarly, insertional analysis in a number of large animal models employing gammaretro and lentiviral vectors revealed polyclonal profiles without enrichment of specific clones after chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations